Provokante Kommunikation: Strategien im politischen Umgang mit transnationalem Terrorismus - Lange, Sebastian (transcript, 2019)
Today the military combat against terrorism of the last decade and a half is considered to be counterproductive – this book shows why the counterterrorism of the last fifteen years has enforced the Jihad movement.